Comprehensive screening for mutations associated with colorectal cancer in unselected cases reveals penetrant and nonpenetrant mutations - Kraus, Cornelia; Rau, Tilman; Lux, Philipp; Erlenbach-Wuensch, Katharina; Loehr, Sabine; Krumbiegel, Mandy; Thiel, Christian; Stoehr, Robert; Agaimy, Abbas; Croner, Roland S.; Stürzl, Michael; Hohenberger, Werner; et al. (International Journal of Cancer, 2015)
Germline mutation testing in patients with colorectal cancer (CRC) is offered only to a subset of patients with a clinical presentation or tumor histology suggestive of familial CRC syndromes, probably underestimating familial CRC predisposition. The aim of our study was to determine whether unbiased screening of newly diagnosed CRC cases with next generation sequencing (NGS) increases the overall detection rate of germline mutations. We analyzed 152 consecutive CRC patients for germline mutations in 18 CRC-associated genes using NGS. All patients were also evaluated for Bethesda criteria and all tumors were investigated for microsatellite instability, immunohistochemistry for mismatch repair proteins and the BRAF*V600E somatic mutation. NGS based sequencing identified 27 variants in 9 genes in 23 out of 152 patients studied (18%). Three of them were already reported as pathogenic and 12 were class 3 germline variants with an uncertain prediction of pathogenicity. Only 1 of these patients fulfilled Bethesda criteria and had a microsatellite instable tumor and an MLH1 germline mutation. The others would have been missed with current approaches: 2 with a MSH6 premature termination mutation and 12 uncertain, potentially pathogenic class 3 variants in APC, MLH1, MSH2, MSH6, MSH3 and MLH3. The higher NGS mutation detection rate compared with current testing strategies based on clinicopathological criteria is probably due to the large genetic heterogeneity and overlapping clinical presentation of the various CRC syndromes. It can also identify apparently nonpenetrant germline mutations complicating the clinical management of the patients and their families.
EVALuna2:6598